SOSIOLOGI MASYARAKAT JEPANG PADA NOVEL UTSUKUSHISA TO KANASHIMI TO DANIZU NO ODORIKOKARYA KAWABATA YASUNARI - Zida Wahyuddin (Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract. This paper is about comparing two literary works in relation to the sociology of literature. Researchers will compare the Japanese society at a given time to locate the equation and the difference in modern literary texts in the form of a novel. The chosen novels are novel Utsu kushi saused to Kanashimi to and Izuno Odoriko. Both of the novels describe the conditions of Japanese people who have the sense of to getherness that manifested through a strong sense of group solidarity. This high loyalty to the group causeda high discipline in Japanese society.Â Keywords: comparative literature, sociology of literature, Japanese society